Resurrection and New Species of the Neotropical Genus Adelonema(Araceae: Philodendron Clade) - Wong, Sin Yeng; Meerow, Alan W.; Croat, Thomas B. (American Society of Plant Taxonomists, 2016)
Previous studies have shown Homalomena as traditionally defined to be polyphyletic, with Neotropical species phylogenetically distinct from Asian species. This study of 29 accessions of 10 Neotropical taxa, and a total of 135 accessions representing 92 taxa of Homalomena, Furtadoa, and Philodendron for nuclear ITS and plastid matK regions, supports resurrection of the genus Adelonema for Neotropical species currently assigned to Homalomena. Adelonema is here delimited as a Neotropical genus of 16 species divided into two new sections: sect. Adelonema and sect. Curmeria, based on morphologically supported molecular results. The genus Adelonema is distinguished by a hypogeal rhizome, crushed vegetative tissues smelling of anise, an extensively sheathing, sometimes prickly petiole, chartaceous often variegated leaf blades, a spadix either obliquely inserted on the spathe/peduncle (sect. Adelonema), or stipitate (sect. Curmeria), ovaries with 2–4-pluriovulate locules, and anatropous ovules on an axile placenta. Four new species are described: Adelonema orientalis, A. palidinervia, A. panamensis, and A. yanamonoensis. Eleven new combinations are made: Adelon